The exotic legume tree species, Acacia mearnsii, alters microbial soil functionalities and the early development of a native tree species, Quercus suber, in North Africa - Boudiaf, I.; Baudoin, E.; Sanguin, H.; Beddiar, A.; Thioulouse, J.; Galiana, A.; Prin, Y.; Le Roux, C.; Lebrun, M.; Duponnois, R. (Soil Biology and Biochemistry, 2013)
Acacia mearnsii is one of the most planted Australian Acacia around the world but is known to be highly invasive, threatening native habitats by competing with indigenous vegetation. The introduction of this species in the Algerian El Kala Biosphere reserve led to the invasion of natural formations to the detri- ment of Quercus suber, a native tree species.We hypothesized that shifts in soil microbial functions and ectomycorrhizal (EcM) fungal community structure triggered by this exotic Acacia species might correlate with a decrease of the early growth of Q. suber. Soil samples were thus collected from 3 different sites where the exotic specieswas at different stages of invasion in the Algerian El Kala Biosphere reserve, (i) a Q. suber forest free of A. mearnsii (site S1), (ii) a Q. suber/A. mearnsii mixed forest where the Australian Acacia has been recently detected (site S2) and (iii) pure stands of A. mearnsii formed more than 20 years ago (site S3). Plant growth, EcM community structure associated with Q. suber roots and soil microbial functionalities were assessed for 6 month-old cultures of Q. suber in glasshouse conditions. The results clearly demonstrated a strong deleterious impact of A. mearnsii invasion level on soil chemical characteristics, microbial functions and EcM community structure and colonization, correlated to a decrease in the early growth of Q. suber seedlings. The current study gives new insights into both the negative impact of exotic species on soil functioning and their effect on indigenous vegetation growth. These results may be used as a basis for improving the conservation practices of native tree species in such degraded areas as a complement of ecological strategies using indigenous ectotrophic early- successional shrub species (eg. Cistus spp.) that our findings have shown to promote EcM multiplica- tion and the early growth of native tree species. 
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Acacia mearnsii; ectomycorrhiza; exotic invasive plant; Soil microbial community

Below-ground ectomycorrhizal community in natural Tuber melanosporum truffle grounds and dynamics after canopy opening. - Garcia-Barreda, Sergi; Reyna, Santiago (Mycorrhiza, 2012)
The ectomycorrhizal fungus Tuber melanosporum fruits in association with Quercus in natural forests of Spain. Some of these stands are managed to keep an open canopy and meet the habitat requirements of the fungus. However, there are few quantitative studies analysing in these forests the relationship between soil environment and T. melanosporum. Eight forest stands which produce T. melanosporum have been monitored for 6 years in order to characterise the below-ground ectomycorrhizal community and to assess its temporal dynamics after experimental canopy opening. The brûlé, the ground where T. melanosporum fruits, shows a distinct ectomycorrhizal community, characterised by lower density of active ectomycorrhizal tips, lower morphotype richness per soil volume, higher abundance of T. melanosporum and lower abundance of Cenococcum geophilum than soil closest to the trunk of the host Quercus ilex. Opening the canopy has not stimulated an increase in T. melanosporum, suggesting that a shift in the soil environment alone will not trigger the formation of new truffières in the short term. The dry climate of these truffières may be a factor as T. melanosporum abundance appears to be sensitive to annual weather conditions.
The following values have no corresponding Zotero field: accession-num: 21932021
Keywords: Brûlé; ectomycorrhiza; Quercus ilex; silviculture; Tuber melanosporum; Wild truffière

Assessment of mycorrhizal colonisation and soil nutrients in unmanaged fire-impacted soils from two target restoration sites - Dias, J. M.; Oliveira, R. S.; Franco, A. R.; Ritz, K.; Nunan, N.; Castro, P. M. L. (Spanish Journal of Agricultural Research, 2010)
The mycorrhizal colonisation of plants grown in unmanaged soils from two restoration sites with a fire history in Northern Portugal was evaluated from the perspective of supporting restoration programmes. To promote restoration of original tree stands, Quercus ilex L. and Pinus pinaster Ait. were used as target species on two sites, denoted Site 1 and 2 respectively. The aim of the study was to assess whether mycorrhizal propagules that survived fire episodes could serve as in situ inoculum sources, and to analyse the spatial distribution of soil nutrients and mycorrhizal parameters. In a laboratory bioassay, P. pinaster and Q. ilex seedlings were grown on soils from the target sites and root colonisation by ectomycorrhizal (ECM) and arbuscular mycorrhizal (AM) fungi was determined. The ECM root colonisation levels found indicated that soil from Site 2 contained sufficient ECM propagules to serve as a primary source of inoculum for P. pinaster. The low levels of ECM and AM colonisation obtained on the roots of plants grown in soil from Site 1 indicated that the existing mycorrhizal propagules might be insufficient for effective root colonisation of Q. ilex. Different ECM morphotypes were found in plants grown in soil from the two sites. At Site 2 mycorrhizal parameters were found to be spatially structured, with signif icant differences in ECM colonisation and soil P concentrations between regions of either side of an existing watercourse. The spatial distribution of mycorrhizal propagules was related to edaphic parameters (total C and extractable P), and correlations between soil nutrients and mycorrhizal parameters were found.
Keywords: arbuscular mycorrhiza; ectomycorrhiza; Pinus pinaster; post fire; Quercus ilex; soil restoration; spatial variation

Can NPK fertilizers enhance seedling growth and mycorrhizal status of Tuber melanosporum-inoculated Quercus ilex seedlings? - Suz, Laura M; Martín, María P; Fischer, Christine R; Bonet, José a; Colinas, Carlos (Mycorrhiza, 2010)
Although successful cultivation of the black truffle (Tuber melanosporum) has inspired the establishment of widespread truffle orchards in agricultural lands throughout the world, there are many unknowns involved in proper management of orchards during the 6-10 years prior to truffle production, and there are conflicting results reported for fertilizer treatments. Here, we systematically evaluate the combined effects of nitrogen, phosphorous, and potassium with different doses of each element, applied to either foliage or roots, on plant growth parameters and the mycorrhizal status of outplanted 3-year-old seedlings in five experimental Quercus ilex-T. melanosporum orchards. Fertilization did not significantly improve seedling aboveground growth, but the plants treated with the fertilizer 12-7-7 applied to the roots (HNr) displayed longer field-developed roots. Only the fertilizer with the highest dose of K (10-6-28) applied to the foliage (HKf) increased the probability of fine root tip colonization by T. melanosporum in field-developed roots. However, the plants treated with the same fertilizer applied to the soil (HKr) presented the highest probability for colonization by other competing mycorrhizal soil fungi. Potassium seems to have an important role in mycorrhizal development in these soils. Apart from T. melanosporum, we found 14 ectomycorrhizal morphotypes, from which seven were identified to species level, three to genus, two to family, and two remained unidentified by their morphological characteristics and DNA analyses.
Keywords: Black truffle; DNAanalysis; ectomycorrhiza; morphotyping; nitrogen; Phosphorous; Potassium; Truffle orchard

Morphological-anatomical characterization and identification of Tomentella ectomycorrhizas. - Jakucs, Erzsébet; Eros-Honti, Zsolt (Mycorrhiza, 2008)
Over the last two decades, much information has been gathered on the ectomycorrhizal fungus community composition of plant associations of boreal, temperate, and tropical regions. Worldwide, Tomentella ectomycorrhizas (ECM) are often common and dominant in the mycorrhizosphere of coniferous and deciduous forests. They are present under different environmental conditions and associate with diverse plant hosts. Tomentella sporocarps, however, are rarely found aboveground, so Tomentella species are often missing from fungus community studies based on fruit-body presence. Tomentella is a resupinate genus of Thelephoraceae (Basidiomycota) forming black-brown, brown, yellow, or ochre ECM on the roots of gymnosperm and angiosperm trees, distinguished by typical morphological-anatomical characteristics (clamped hyphae, angular mantle, surface network, special rhizomorphs and cystidia). In this paper, we review the taxonomic position and morphological-anatomical characteristics of Tomentella ECM. A short summary of the microscopic features used for distinguishing tomentelloids during morphotyping and identification is presented in order to support molecular and ecological studies of ectomycorrhizal fungus communities.
Keywords: Anatomy; ECM; ectomycorrhiza; identification; morphology; Tomentella

Cultivation of black truffle to promote reforestation and land-use stability - Bonet, J A; Fischer, C R; Colinas, C (Agron. Sustain. Dev., 2006)
Cultivation of black truffle, Tuber melanosporum Vitt., has become an important agricultural alternative in rural Mediterranean regions due to its success in relatively harsh conditions, its high market value and diminishing production in natural areas. In addition, truffle cultivation requires relatively low agricultural inputs, promotes reforestation and economic restoration of rural lands and land-use stability. However, there remain major issues regarding the management practices to ensure successful black truffle production. We therefore conducted an experiment to evaluate 3 levels of irrigation based on monthly water deficit and the effects of currently applied weed control systems and fertilization. Treatment effects were evaluated by examining the mycorrhizal status of out-planted 1-yr-old Quercus ilex L. seedlings and seedling growth parameters after 18 months in 3 distinct experimental truffle plantations located in the foothills of the Spanish Pyrenees. We found that replacing one-half of the water deficit of the driest month (moderate irrigation) promoted the proliferation of T. melanosporum mycorrhizae, while high irrigation reduced fine root production and truffle mycorrhizae. Glyphosate weed control improved seedling survival by up to 16% over control seedlings without jeopardizing truffle mycorrhizae in the first year. Fertilization did not improve seedling growth or influence its mycorrhizal status. We describe the persistent relationship between this ectomycorrhizal fungus and Q. ilex by quantifying old and new mycorrhizae and we discuss the ecological implications of the symbiosis
Keywords: agricultural alternative; ectomycorrhiza; Quercus ilex; water deficit

Cultivation of black truffle to promote reforestation and land-use stability - Bonet, J. A.; Fischer, C. R.; Colinas, C. (Agron. Sustain. Dev., 2006)
Cultivation of black truffle, Tuber melanosporum Vitt., has become an important agricultural alternative in rural Mediterranean regions due to its success in relatively harsh conditions, its high market value and diminishing production in natural areas. In addition, truffle cultivation requires relatively low agricultural inputs, promotes reforestation and economic restoration of rural lands and land-use stability. However, there remain major issues regarding the management practices to ensure successful black truffle production. We therefore conducted an experiment to evaluate 3 levels of irrigation based on monthly water deficit and the effects of currently applied weed control systems and fertilization. Treatment effects were evaluated by examining the mycorrhizal status of out-planted 1-yr-old Quercus ilex L. seedlings and seedling growth parameters after 18 months in 3 distinct experimental truffle plantations located in the foothills of the Spanish Pyrenees. We found that replacing one-half of the water deficit of the driest month (moderate irrigation) promoted the proliferation of T. melanosporum mycorrhizae, while high irrigation reduced fine root production and truffle mycorrhizae. Glyphosate weed control improved seedling survival by up to 16% over control seedlings without jeopardizing truffle mycorrhizae in the first year. Fertilization did not improve seedling growth or influence its mycorrhizal status. We describe the persistent relationship between this ectomycorrhizal fungus and Q. ilex by quantifying old and new mycorrhizae and we discuss the ecological implications of the symbiosis
Keywords: agricultural alternative; ectomycorrhiza; Quercus ilex; water deficit

The influence of mycorrhization with Tuber melanosporum in the afforestation of a Mediterranean site with Quercus ilex and Quercus faginea - Domínguez Núñez, José Alfonso; Serrano, Jesús Selva; Barreal, José Antonio Rodríguez; González, José Antonio Saiz De Omeñaca (Forest Ecology and Management, 2006)
A Holm oak (Quercus ilex L.) and Lusitanian oak (Quercus faginea) stand establishment, mycorrhizated with black trufﬂe (Tuber melanosporum Vitt.), situated in the north of Alicante, south-eastern Spain, was analyzed during the second year of plantation. The mycorrhization improved seedling growth, especially that of the shoots, encouraged water uptake of the seedlings during the summer drought, and improved total phosphorus absorption. Tuber melanosporum was found to colonize the roots of the seedlings very successfully
Keywords: ectomycorrhiza; Nutrients; quercus faginea lamk; Quercus ilex L; Reforestation; tuber melanosporum vitt; water stress

Estado hídrico y demanda de fotosintesis de Quercus ilex, Quercus faginea y Pinus halepensis MICORRIZADOS ARTIFICIALMENTE CON Tuber melanosporum EN VIVERO - DOMÍNGUEZ, J. A.; R. PLANELLES; RODRÍGUEZ BARREAL, J. A.; SAÍZ DE OMEÑACA, J. A.; ZAZO, J.; TEYSSIERE, M.; MARTINEZ, G.; PINAZO, O. (III Congreso Forestal Español Congreso, 2001)
We have been carried out a periodic control in Quercus ilex, Quercus faginea and Pinus halepensis inoculated with Tuber melanosporum Vitt. during the first year of growth in nursery with a water-non stressed régime; in all the species, the minimum water potential and transpiration rate didn't reflect any differences for the treatment, but in some cases, the photosynthesis rate was major in inoculated seedlings. K.W.:
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: ectomycorrhiza; photosynthesis; Pinus halepensis; Quercus faginea; Quercus ilex; Tuber

Estado hídrico y demanda de fotosintesis de Quercus ilex, Quercus faginea y Pinus halepensis MICORRIZADOS ARTIFICIALMENTE CON Tuber melanosporum EN VIVERO - DOMÍNGUEZ, J A; R. PLANELLES; RODRÍGUEZ BARREAL, J A; SAÍZ DE OMEÑACA, J A; ZAZO, J; TEYSSIERE, M; MARTINEZ, G; PINAZO, O (III Congreso Forestal Español Congreso, 2001)
We have been carried out a periodic control in Quercus ilex, Quercus faginea and Pinus halepensis inoculated with Tuber melanosporum Vitt. during the first year of growth in nursery with a water-non stressed régime; in all the species, the minimum water potential and transpiration rate didn't reflect any differences for the treatment, but in some cases, the photosynthesis rate was major in inoculated seedlings. K.W.:
Keywords: ectomycorrhiza; photosynthesis; Pinus halepensis; Quercus faginea; Quercus ilex; Tuber

Synthesis of mycorrhizas on Quercus suber using Hebeloma sinapizans and Paxillus involutus - Branzanti, Barbara; Zambonelli, Alessandra (Agriculture, Ecosystems & Environment, 1990)
Hebeloma sinapizans and Paxillus involutus formed ectomycorrhizae with cork oak (Quercus subedotr) in axenic conditions and glasshouse trials. Inoculation with H. sinapizans, but not P. involutus, prevented the contamination of seedlings by Sphaerosporella brunnea. Whereas H. sinapizans formed mycorrhizas with a majority of feeder roots, P. involutus formed mycorrhizas with a minority.
Keywords: contamination prevention (PG); ectomycorrhiza; Quercus suber